Adenomatoid Odontogenic Tumor as a Confusing Maxillary Gingival Swelling - Kanungo, Bindu (Journal of Orofacial Research, 2014)
Maxillary gingival swelling encompasses a diverse group of lesions although clinically they are uncharacteristic. Adenomatoid odontogenic tumor (AOT) is one such uncommon cause of gingival swelling which is often misdiagnosed as other odontogenic lesions. AOT is a rare, slow growing, expansile, noninvasive, benign odontogenic epithelial tumor with relative frequency of 2.2 to 7.1%. It is predominantly found in young females, particularly in the second decade of life. It has apredilection for the anterior maxilla and frequently associated with unerupted permanent canines. AOT appears in three clinicotopographic variants: follicular, extrafollicular and peripheral. Histogenesis of AOT is uncertain. Some accept it as hamartoma while others argue in favor of true neoplasm. Treatment is conservative and the prognosis is excellent. We report a case of follicular variant of AOT in the right maxillary anterior region in a 14-year-old girl. The tumor was slow growing and was clearly encapsulated suggesting its benign behavior